Adherence to oral migraine-preventive medications among patients with chronic migraine. (May 2015) - Hepp, Zsolt; Dodick, David W; Varon, Sepideh F; Gillard, Patrick; Hansen, Ryan N; Devine, Emily B
Background: Chronic migraine (CM) is a disabling disorder characterized by ≥15 headache days per month that has been shown to significantly reduce quality of life. Migraine-prevention guidelines recommend preventive medications as the standard of care for patients with frequent migraine. The aim of this study was to assess adherence to 14 commonly prescribed oral migraine-preventive medications (OMPMs) among patients with CM. Methods: Retrospective claims analysis of a US claim database (Truven MarketScan® Databases) was queried to identify patients who were at least 18 years old, diagnosed with CM, and initiated an OMPM (antidepressants, beta blockers, or anticonvulsants) between January 1, 2008 and September 30, 2012. Medication possession ratios (MPR) and proportion of days covered (PDC) were calculated for each patient. A cutoff of ≥80% was used to classify adherence. The odds of adherence between OMPMs were compared using logistic regression models. Results: Of the 75, 870 patients identified with CM, 8688 met the inclusion/exclusion criteria. Adherence ranged between 26% to 29% at six months and 17% to 20% at 12 months depending on the calculation used to classify adherence (PDC and MPR, respectively). Adherence among the 14 OMPMs was similar except for amitriptyline, nortriptyline, gabapentin, and divalproex, which had significantly lower odds of adherence when compared to topiramate. Conclusion: Adherence to OMPMs is low among the US CM population at six months and worsens by 12 months.